The in vitro cellular immune response to quartz - Surcel, D; Gabor, S; Abraham, A; Ramboiu, S (Journal of hygiene, epidemiology, microbiology, and immunology, 1987)
It is known that macrophages release into medium in vitro biologically active substances which modulate immune response. In recent years, increase attention has been directed towards the role of prostaglandin in macrophage function. Guinea pig splenic lymphocytes and peritoneal macrophage cultures were incubated with quartz (DQ12), Corundum and aspirin as prostaglandin inhibitor. Lymphocyte proliferation measured by 3H-thymidine incorporation, and lymphokine release by Bendixen-Soborg capillary test (MIF) were applied. EA rosetting and phagocytosis were determined for macrophage function assessment. Quartz suppressed the immune response evidenced by reduced 3H-thymidine incorporation and decreased lymphokine production. Aspirin (as a specific prostaglandin synthesis inhibitor) restored the affected by quartz immunological parameters. This observation gives support to the hypothesis that the immunological response to quartz involves macrophage prostaglandin release, presumably as a first step of lipid peroxidation.
Keywords: Prostaglandins; techniky in vitro; Immunity, Cellular; Macrophage Migration-Inhibitory Factors; T-Lymphocytes; inhibiční faktory migrace makrofágů; Macrophage Activation; Silicon Dioxide; makrofágy; zvířata; Lymphocyte Activation; Guinea Pigs; imunosupresivní léčba; buněčná imunita; křemen; aktivace lymfocytů; aktivace makrofágů; prostaglandiny; Immunosuppression Therapy; morčata; oxid křemičitý; In Vitro Techniques; T-lymfocyty; Animals; Macrophages; Quartz